Cytochrome P450 26A1 Modulates the Polarization of Uterine Macrophages During the Peri-Implantation Period - Ji, Wen-Heng; Li, Dan-Dan; Wei, Dan-Ping; Gu, Ai-Qin; Yang, Ying; Peng, Jing-Pian (Frontiers in Immunology, 2021)
Uterine M1/M2 macrophages activation states undergo dynamic changes throughout pregnancy, and inappropriate macrophages polarization can cause adverse pregnancy outcomes, especially during the peri-implantation period. Our previous studies have confirmed that Cytochrome P450 26A1 (CYP26A1) can affect embryo implantation by regulating uterine NK cells and DCs. The aim of this study was to investigate whether CYP26A1 regulates the polarization of uterine macrophages in early pregnancy. Here, we observed that Cyp26a1 was significantly upregulated in M1 as compared with M2 of uterine macrophages, Raw264.7 and iBMDM. Knockdown of CYP26A1 in mice uterine significantly decreased the number of embryo implantation sites and the proportion of CD45+F4/80+CD206− M1-like uterine macrophages. Primary uterine macrophages treated with anti-CYP26A1 antibody expressed significantly lower levels of M1 markers Nos2, Il1b, Il6 and Tnf-a. In CYP26A1 knockout Raw264.7 cells, the protein levels of M1 markers TNF-α, IL-6 and CD86 were significantly decreased as compared with the wild type cells. Moreover, CYP26A1 deficiency decreased the ability to produce nitric oxide and increased the phagocytosis capacity of Raw264.7 cells under M1 stimulation state. The re-introduction of CYP26A1 partially reversed the polarization levels of M1 in CYP26A1 knockout Raw264.7 cells. CYP26A1 may regulate the polarization of uterine macrophages to M1 through Stap1 and Slc7a2. In summary, these results indicate that CYP26A1 plays a significant role in macrophage polarization, and knockdown of CYP26A1 can cause insufficient M1 polarization during the peri-implantation period, which has adverse effects on blastocyst implantation.